Yerli Sosyolojinin İmkânı Olarak Baykan Sezer - Koyuncu, Ahmet Ayhan; Bozkurt, Recep (Muş Alparslan Üniversitesi, 2019)
In the19th century, sociology emerged with the efforts to solve the problems in theWest. Sociology has been used instrumentally for the new social problems thatemerged in the West, the search for order against these problems and thesolution of the problems of legitimacy of world sovereignty. Sociology emergedas a product of the West's own internal dynamics. But in our country, Sociologypresented as a prescription for the problems of Turkish society by taking therecipes developed against the problems of the West. However, Turkish sociologydid not consist entirely of this imitator and transporter approach. One of theoriginal / local contributions in this direction is Baykan Sezer. Sezer pointedout the necessity of building a, Turkish Sociology that is appropriate to theconditions of the Turkish society, by taking and evaluating our problems withinthe framework of East-West relations and conflict, explaining our socialstructure and establishing a relationship with our tradition of thought and ourhistory. Sezer, influenced by Kemal Tahir, tried to understand the Turkishsociety and its problems within the East-West dilemma by putting historicity inthe center of sociology.The study will try to discuss the views of Sezer as anopportunity of Turkish sociology.

19.yüzyılda Batı’da yaşanan sorunlara çözüm getirme çabalarıyla sosyoloji bilimi ortayaçıkmıştır. Batı’da ortaya çıkan yeni toplumsal sorunlar ve bu sorunlara karşıdüzen arayışı ve dünya egemenliğinin meşruluğu problemlerinin çözümü için sosyolojiaraçsal bir şekilde kullanılmıştır. Ülkemizde Batı’nın sorunlarına karşıgeliştirilen çözüm reçeteleri alınıp Türk toplumunun sorunlarına hazır reçeteolarak sunulmuştur. Ancak Türk sosyolojisi bütünüyle bu taklitçi ve nakilciyaklaşımdan ibaret olmamıştır. Bu yöndeki özgün/yerli katkılardan biri BaykanSezer’dir. Sezer, Türk toplumunun sorunlarını Doğu-Batı ilişkileri ve çatışmasıçerçevesinde ele alıp değerlendiren, sosyal bünyemizi açıklayan, düşüncegeleneğimiz ve tarihimizle ilişki kuran bir “Türk Sosyolojisi” inşa etmekaygısında olmuştur. Sezer, Kemal Tahir’den etkilenerek sosyoloji bilimininmerkezine tarihselliği koyarak Doğu-Batı ikilemi içerisinde Türk toplumunuanlamaya çalışmış, Türk sosyolojisinde yerlilik üzerinde durmuştur. Buçalışmada Türk sosyolojisinin bir imkânı olarak Sezer’in görüşleri elealınacaktır.
Baykan Sezer As the Possibility of Native Sociology
anemon
Keywords: Western Sociology; Turkish Sociology; Kemal Tahir; Baykan Sezer; East-West Conflict; Native Sociology; Batı Sosyolojisi; Türk Sosyolojisi; Kemal Tahir; Baykan Sezer; Doğu-Batı Çatışması; Yerli Sosyoloji